Kommunikasie(-kunde) in Suid-Afrika - H.C. Marais (Communicare)
THIS article represents a review of trends in the development of Communication as academic discipline In South Africa. Sallent results of a number of surveys are the following: (a) large number of students have graduated over the past ten years (B degrees -3279; Honours = 489; Masters = 82 and at least 22 doctorates). Wide differences in post-graduate penetration be tween universities are also noticeable (see tables 1 and 2; (b) Mass communication is at present the single most frequently offered course in university communication curricula while theory and methodology as indepen dent communication courses figure fairly prominently. Speech and interpersonal com munication are not salient in university courses (see figure 1); (c) Since 1980 a total of 182 research projects in communication have been completed. As in the case of teaching, mass communication has been the most popular field of research. In contrast hardly any research on methodological problems have been under taken over the past seven years (see figure 2); (d) Analysis of applications by com munication students and researchers for financial support from the HSRC indicated that their success rates have been lower than comparable disciplines (see figure 3). Against the background of the importance and relevance of communication to contemporary South African society the paper concludes with a number of interpretations and future challenges